Prevalence, factors associated with, and consequences of long COVID symptoms in people diagnosed with Coronavirus disease 2019 (COVID-19) at Sida Hospital, Nakhon Ratchasima province, Thailand - Ponkkaa , Sujittra; Phuengnam, Kornkan; Sadkuntod, Niwat; Prommanta, Teerapat (Disease Control Journal, 2024)
This cross-sectional descriptive study investigated the prevalence, relevant factors, and consequences of long COVID symptoms through telephone follow-up with the patients at Sida Hospital, Nakhon Ratchasima province, who were diagnosed with COVID-19 and discharged between 9 and 12 months. The results showed that 186 of 220 patients (84.5%) reported experiencing at least one of long COVID symptoms. They experienced two or three long COVID symptoms among fourteen symptoms on average. Fatigue (82.3%), muscle pain (33.6%), memory issues (33.6%), and sleeping difficulties (10.5%) ranked as the most prevalent symptoms. Female (AOR=2.71; 95% CI: 1.25-5.87) and the level of symptoms of COVID-19 disease on admission (AOR=7.89; 95% CI: 2.34-26.63) were significantly related to long COVID symptoms (p<0.05). The effects of long COVID symptoms are not limited only to physical health, but they also affect emotional (COR=3.93; 95% CI; 1.33-11.66) and mental health (COR=3.84; 95% CI: 1.70-8.69). Therefore, dedicated policies and guidelines should be established and implemented to support patients suffering from long COVID symptoms, both in the hospital and in the community. The program should be developed for assessing the symptoms, risks, and consequences of long COVID, as well as enhancing people’s ability to manage long-term symptoms and consequences of the disease.